Analysis of an Effective Antibiotic (Chaetomacin) Isolated from a Thermophilic Bacillus sp. Against Olive Green Mold - Tautorus, T. E. (1984)
Successful methods to control the damaging weed mold Chaetomium olivaceum (olive green mold) in mushroom beds are not known. An effective antibiotic (named chaetomacin) against C. olivaceum was isolated from a thermophilic Bacillus sp. This compound was shown to be an extremely potent and stable antibiotic, effective over a wide range of both pH (2 to 10) and temperature (−15 to 150°C). Chaetomacin is soluble in most polar solvents and insoluble in nonpolar solvents. It is produced only at mesophilic temperatures and is also active against other Bacillus spp. and various eucaryotes, but it demonstrates no activity against gram-negative rods or gram-positive cocci. Final purification of chaetomacin was accomplished through thin-layer chromatography on silica gel analytical plates. Amino acid analysis revealed the antibiotic to be a peptide, acidic in nature. Examination of the literature reveals no other previously isolated antibiotics identical to chaetomacin.